To The Lighthouse - Woolf, Virginia; Introduction by Boland, Eavan and Ellmann, Maud (London Vintage Books, 2004)
From the seemingly trivial postponement of a visit to a nearby lighthouse, author Virginia Woolf constructs a remarkable and moving examination of the complex tensions and allegiances of family life, and the conflict between male and female principles.
This ed. originally published: 2000.
Keywords: Married people -- Scotland--Island of Skye -- Lighthouses